Meningkatkan Tata Kelola Organisasi Petani dan Manajemen Produksi Pertanian melalui Pelatihan Pembuatan Pupuk Organik Cair - Milawati Valantia; Try Adhi Bangsawan; Novia Safitri; Santi Santi; Fatiah Rahmah (Jurnal Pengabdian Masyarakat Waradin, 2024)
Improving farmer organizational governance and crop production management are important aspects in achieving sustainable agriculture. This study aims to evaluate the impact of training on liquid organic fertiliser production on improving farmer organisation governance and crop production management in Mekar Agung Village. The training was attended by 30 purposively selected farmer organisation members. The research methodology used a quantitative approach with a pretest-posttest design. The pretest results showed that participants' initial knowledge of liquid organic fertiliser production and farmer organisation governance was at a low level. However, the posttest results showed a significant improvement after the training, with the average score increasing from 55% to 85%. The study concluded that the training on liquid organic fertiliser production was effective in improving farmers' organisational capacity and crop production management in Mekar Agung Village, and has positive implications for the sustainability of agriculture in the area.